Deactivation Mechanism and Enhanced Durability of V2O5/TiO2–SiO2–MoO3 Catalysts for NH3−SCR in the Presence of SO2. Issue 23 (11th October 2020) - Kuma, Ryoji; Kitano, Tomoyuki; Tsujiguchi, Takuya; Tanaka, Tsunehiro
Abstract: V2 O5 /TiO2 ‐type catalysts are widely applied for selective catalytic NO reduction by NH3 (NH3 ‐SCR), but enhanced sulfur tolerance and low‐temperature activity are required. Herein, V2 O5 /TiO2 −SiO2 −MoO3 (V/TSM) was demonstrated to have excellent catalytic activity and durability for NH3 ‐SCR in the presence of SO2 at temperatures lower than 200 °C. The deactivation mechanism and factors influencing SO2 durability were investigated using catalytic durability tests, Fourier‐transform infrared spectroscopy, and temperature‐programmed desorption/decomposition. Our results revealed that (NH4 )2 S2 O3 and NH4 HSO4 form on catalyst surfaces by NH3 −SO2 −H2 O reactions at low temperatures, resulting in catalyst deactivation via pore blockage. However, V/TSM was found to possess an increased number of active sites for decomposing deposited ammonium sulfate salts. The decomposition activity was related to the solid acidity, which enhanced SO2 desorption and reactions between ammonium sulfate salts and NO. These findings will contribute to the development of catalysts with improved lifetimes for NH3 −SCR. Abstract : NH3 ‐SCR : V2 O5 /TiO2 −SiO2 −MoO3 exhibits superior activity and durability for selective catalytic NO reduction by NH3 in the presence of SO2 . The SO2 durability does not originate from suppressing SO2 adsorption but from enhancing the decomposition of deposited ammonium sulfate salts owing to the high acid site density of this catalyst.